(untitled) (Research, Society and Development, 2022)
To validate educational technology for prevention and treatment of patients with pressure injury. This is an methodological research, developed in two phases: elaboration and evoluation. Accomplished from November 2020 to February 2022, in teaching hospital, and performed with care nurses and managers. A questionnaire was used based on the Likert to evaluate the content scale to validate the professional. Participants were 15 judges, all working in care and in the workplace with high incidence and prevalence of pressure injury. All specialists worked in the area of prevention and treatment of pressure injury. Data were analyzed using Cronbach’s alpha coefficient, content validity index and leved of agreement. That study reinforces that the work process in health increasingly needs investment, safety and innovation through the use of health technologies to assist nurses in making decisions efficiently and effectively in the management of the prevention and treatment of pressure injury.